2018
DOI: 10.1038/s41419-018-0646-2
|View full text |Cite
|
Sign up to set email alerts
|

REGγ deficiency suppresses tumor progression via stabilizing CK1ε in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is the most common malignant disease of kidney in adults. The proteasome activator REGγ was previously reported to promote the degradation of multiple important regulatory proteins and involved in the progression and development of numerous human cancers. Here, we first reported that REGγ was upregulated in RCC and its upregulation was correlated with a poor prognosis in RCC patients. REGγ depletion obviously suppressed RCC cells proliferation in vitro and in vivo. Notably, casein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…Murata et al found that REG γ-deficient mice display growth retardation compared with wild type mice. Meanwhile, previous studies reported that REG γ was strongly implicated in many kinds of cancer cells proliferation (Chen et al 2018;Li et al 2015a;Zhang et al 2012). Our results are consistent with these data, indicating that REG γ plays a critical role in osteosarcoma proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Murata et al found that REG γ-deficient mice display growth retardation compared with wild type mice. Meanwhile, previous studies reported that REG γ was strongly implicated in many kinds of cancer cells proliferation (Chen et al 2018;Li et al 2015a;Zhang et al 2012). Our results are consistent with these data, indicating that REG γ plays a critical role in osteosarcoma proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, we found that proapoptotic protein (caspase-3) level was significantly increased, while antiapoptotic protein (bcl-2) was decreased following REG γ knockdown. Present results were supported by previous researches (Chen et al, 2018;Moncsek et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…To seek further the underlying mechanism that REG γ prompting human osteosarcoma proliferation, we used RNA interference to reduce REG γ expression in MG-63 and SaoS-2 human osteosarcoma cell lines, then performed cell-cycle profile and apoptosis analysis by flow cytometry and measured the cell cycle and apoptosis related proteins level. Knockdown of REG γ lead more cells to be arrested at the G0/G1 phase in our experiments, that was parallel with other independent studies on prostate cancer cells (Chen et al, 2017) and renal carcinoma cells (Chen et al, 2018). However, another study also demonstrated that REG γ downregulation resulted in cell cycle arrest at the G2/M phase in HeLa cells (Chen et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations